QUANTIFICATION OF CHLORELLA - ALGAE BY IMAGE ANALYSIS - S.LAKSHMI,; R.SIVAKUMAR, (International Journal of Pharma and Bio Sciences, 2016)
In order to raise the production it is necessary to monitor the growth of the algae periodically. The main aim of this work is to develop an automated tool that provides reliable and accurate results for counting the chlorella algae cells from the images taken from chlorella ponds. Recent developments in computer image analysis techniques allow more accurate quantification of algae growth in ponds through images which are taken by microscopic enabled mobile phones. In this paper, we propose a technique for quantifying the chlorella algae to increase the production using Image J software, which is freely available over the internet. This software includes the methods for calibrating measurements, scaling the images, assessment of the size of the object and its thickness, cell counting and analysis of area. The counting has been done on several microscopic images and finally discussion has been made by comparing the results achieved by the proposed method and the conventional manual counting method. The proposed method is very simple and easy one.